Learning english in kindergarten, from the parents’ and from an education science perspective (Training and Practice : Journal of Educational Sciences, 2020)
Today basic English proficiency is required in everyday life. For most English speakers, English is a second language. However, opinions differ with regard to the age at which second language learning should start. There is an increasing evidence on the importance of the first years of life from the perspective of effective language acquisition. The learner’s age seems to play a key role in various aspects of learning a language. Nonetheless, a considerable number of parents are wary of early second language learning. Here I study how the parents’ level of education, English proficiency, and age correlate with their opinion about early second language learning at kindergarten.